2021
DOI: 10.2147/idr.s294611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant Tuberculosis in Dalian, China: A Retrospective Study

Abstract: Purpose Multidrug-resistant tuberculosis (MDR-TB) is the cause of serious health and economic burdens worldwide. The present study aimed to explore the initial and acquired drug-resistance rates among TB patients from 2012 to 2019 in Dalian, China. The effectiveness of MDR-TB prevention and control strategies were then evaluated. Patients and Methods Drug susceptibility testing (DST) was performed for 6429 diagnosed, culture-positive, Mycobacterium tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Dalian, which is located in northeast China, has a residential population of 6.95 million, and suffers from a high TB burden. 27 The incidence of TB was 52.8 per 100,000, and new MDR/RR-TB cases accounted for 4.8% in the region, higher than the global level. 27 In Dalian, information from all TB patients is collected regularly with TB surveillance and management through the China Information System for TB Prevention and Control.…”
Section: Study Populationmentioning
confidence: 90%
See 1 more Smart Citation
“…Dalian, which is located in northeast China, has a residential population of 6.95 million, and suffers from a high TB burden. 27 The incidence of TB was 52.8 per 100,000, and new MDR/RR-TB cases accounted for 4.8% in the region, higher than the global level. 27 In Dalian, information from all TB patients is collected regularly with TB surveillance and management through the China Information System for TB Prevention and Control.…”
Section: Study Populationmentioning
confidence: 90%
“…27 The incidence of TB was 52.8 per 100,000, and new MDR/RR-TB cases accounted for 4.8% in the region, higher than the global level. 27 In Dalian, information from all TB patients is collected regularly with TB surveillance and management through the China Information System for TB Prevention and Control. TB cases in the study were diagnosed by sputum smear examination, sputum culture or the WHO clinical criteria from Jan 1, 2014, to Dec 31, 2019.…”
Section: Study Populationmentioning
confidence: 90%
“…There is a high prevalence of TB in Dalian. 15 The incidence of TB in the region is 52/100,000, which is well above the global average. 16 However, the Directly Observed Treatment and Short Course (DOTS) strategy and the Global Fund for MDR-TB Prevention and Treatment project have been implemented in this region since 2012.…”
Section: Introductionmentioning
confidence: 93%
“… 16 However, the Directly Observed Treatment and Short Course (DOTS) strategy and the Global Fund for MDR-TB Prevention and Treatment project have been implemented in this region since 2012. 15 Many patients with suspected DR-TB are diagnosed in Dalian every year, and these patients can easily develop MDR-TB or even XDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the drug-resistant rate of tuberculosis is essential, especially in areas with high tuberculosis rates, including the Southeast and the Mekong Delta 3 . Recently, many studies have been published that found rates of TB resistance in Ha Noi, Vietnam (2019) 4 , India (2020) 5 , Dalian, China (2021) 6 . However, few studies have been conducted to establish the proportion of drug resistance in Can Tho City (Mekong Delta).…”
Section: Introductionmentioning
confidence: 99%